PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2014-2018 - T. Aslam Deliar Rahman; Muhammad Karya Satya Azhar; Ahmad Sani (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2023)
This research aims to determine empirically the influence of profitability, liquidity, leverage, dividend policy and company size on company value. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. Sampling was determined using the purposive sampling method. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is multiple regression analysis. The results shown in this study show that profitability ratios are proxied by Return on Assets (ROA), liquidity is proxied by Current Ratio (CR), dividend policy is proxied by Dividend Payout Ratio (DPR), and company size is proxied by The natural logarithm of total assets has an effect on company value, while leverage proxied by the Debt to Equity Ratio (DER) has no effect on company value. The research results show that return on assets has a significant effect on company value, the current ratio has a significant effect on company value, the Dividend Payout Ratio has a significant effect on company value, company size has a significant effect on company value and there is no significant effect of the Debt to Equity Ratio on company value.